Providing Fe Tablets to Prevent Anemia in Pregnant Women in Kesambe Lama Village, East Curup District - Putri Dafi, Tria Anugrah; Seupeng, Teuku Michael; Monica , Tiara; Lensiana, Lensiana; Wijayati , Anteng; Putri , Yesi (Universitas Dehasen Bengkulu, 2025)
Consumption of Fe tablets in pregnant women is very important in meeting the nutritional needs of the fetus, such as preventing anemia in pregnant women, reducing the risk of death in mothers due to postpartum hemorrhage. Iron (Fe) tablets or blood supplement tablets (TTD) are supplements containing iron and folate given to pregnant women to prevent iron nutritional anemia during pregnancy which functions as a form of hemoglobin (Hb) in the blood. This activity aims to overcome the incidence of anemia in pregnant women and understand the benefits of consuming Fe tablets during pregnancy by using the lecture method with the help of leaflets then continuing with the distribution of Fe tablets. Participants in this activity were 20 pregnant women from the first trimester to the third trimester. The assessment was carried out by measuring participants' knowledge about the benefits of consuming Fe tablets by conducting a question and answer session before and after being given the counseling material. The results of the activity evaluation showed that the target number was 75% of pregnant women who had received Fe tablets, and the result was that 80% of pregnant women had received Fe tablets. So it can be concluded that the participants understand the importance of the benefits of iron tablets for pregnant women